Finding Intersections and Normalizers in Finitely Generated Nilpotent Groups. - LO, E. H.
We present algorithms for computing intersections, normalizers and subgroup products of subgroups in finitely generated nilpotent groups given by nilpotent presentations. The problems are reduced to solving for certain minimal solutions in linear Diophantine equations over the integers. Performance of the algorithm using a Mathematica implementation is demonstrated.